Facebook Society : Losing Ourselves in Sharing Ourselves - Simanowski, Roberto (Columbia University Press, 2018)
Facebook claims that it is building a "global community." Whether this sounds utopian, dystopian, or simply self-promotional, there is no denying that social-media platforms have altered social interaction, political life, and outlooks on the world, even for people who do not regularly use them. In this book, Roberto Simanowski takes Facebook as a starting point to investigate our social-media society-and its insidious consequences for our concept of the self.Simanowski contends that while they are often denounced as outlets for narcissism and self-branding, social networks and the practices they cultivate in fact remake the self in their image. Sharing is the outsourcing of one's experiences, encouraging unreflective self-narration rather than conscious self-determination. Instead of experiencing the present, we are stuck ceaselessly documenting and archiving it. We let our lives become episodic autobiographies whose real author is the algorithm lurking behind the interface. As we go about accumulating more material for the platform to arrange for us, our sense of self becomes diminished-and Facebook shapes a subject who no longer minds. Social-media companies' relentless pursuit of personal data for advertising purposes presents users with increasingly targeted, customized information, attenuating cultural memory and fracturing collective identity. Presenting a creative, philosophically informed perspective that speaks candidly to a shared reality, Facebook Society asks us to come to terms with the networked world for our own sake and for all those with whom we share it.